Differences in alcohol consumption and drinking patterns in Ghanaians in Europe and Africa: The RODAM Study. - Juliet Addo; Sarah Cook; Cecilia Galbete; Charles Agyemang; Kerstin Klipstein-Grobusch; Mary Nicolaou; Ina Danquah; Matthias B Schulze; Rachel Brathwaite; Frank P Mockenhaupt; Erik Beune; Karlijn Meeks; et al. (PLoS ONE, 2018)
BACKGROUND:Little is known about alcohol consumption among Africans living in rural and urban Africa compared to African migrants in Europe. We compared the patterns of alcohol consumption in a group of Ghanaians living in different locations in Ghana and in Europe and examined the factors associated with drinking alcohol. METHODS:Data were from a cross-sectional study (RODAM) of Ghanaians aged 25-70 years living in rural and urban Ghana and in Amsterdam, Berlin and London. Information on how often participants consumed at least one standard alcoholic drink in the preceding 12 months, the type of alcoholic beverage and the average serving size was obtained using a food propensity questionnaire. The associations between drinking alcohol and socio-demographic variables, and frequency of attending religious services were investigated using logistic regression models stratified by site and sex. For Ghanaians living in Europe, the number of years since migration and acculturation were also included in the model as covariates. RESULTS:4280 participants (62.2% women) were included in the analyses. In both men and women, the prevalence of drinking and amount of alcohol consumed per day was highest in Berlin (prevalence of drinking 71.0% and 61.7%) and lowest in urban Ghana (41.4% and 26.8%). After adjustment for age and education in both men and women in Europe, those attending religious services less frequently reported higher levels of drinking alcohol than non-attendants (never attend/no religion compared to attending service at least once a week men OR 4.60 95% CI 2.85, 7.44; women OR 1.80 95% CI 1.12, 2.90) p-trend with frequency <0.001 in men; 0.002 in women); this association was seen also in men in rural Ghana (p-trend = 0.001) and women in urban Ghana (p-trend = 0.02). The prevalence of drinking was positively associated with years since migration in both men and women in Europe ((OR per years increase in time lived in Europe 1.25 (95% CI 1.02,1.53) test for trend p = 0.03 in women; OR 1.29 (95% CI 1.03, 1.62 p = 0.03 in men) but no association was found with self-reported measures of acculturation (ethnic identity, cultural orientation or social networks). CONCLUSION:There are marked differences in alcohol consumption between Ghanaians living in Europe and in Ghana suggesting migration has an important influence of drinking patterns and also suggesting the possibility of requiring different strategies in alcohol reduction campaigns among Ghanaians in different locations.